A new species of Nagumoea (Bacillariophyta) from Antarctica, and a further consideration of the systematic position of the genus - van De Vijver, Bart; Kociolek, J. Patrick (Phytotaxa, 2018)
Nagumoea livingstonensis sp. nov., a new diatom species is described from a coastal pool on the Maritime Antarctic Livingston Island, South Shetland Islands, based on light and scanning electron microscopy observations. A morphological comparison is made with the two other known Nagumoea taxa. The new species can be separated by the clear hyaline line between the valve face and mantle areolae, differences in the structure of its a scalariform valvocopula and broader fibulae. The taxonomic position of the genus Nagumoea is discussed. A placement within the Rhopalodiales is doubtful based on the absence of clover-shaped areolae coverings in Nagumoea making the order of Bacillariales a more probable position.